The measurement of implicit and explicit knowledge. Issue 2 (4th March 2021) - Ellis, Rod; Roever, Carsten
ABSTRACT: This article presents a review of research that has investigated ways of measuring implicit and explicit knowledge of a second language (L2), focusing on grammar. It begins by defining implicit and explicit knowledge in terms of a distinguishing set of criteria. Two ways of investigating implicit knowledge are discussed – through experimental studies of implicit learning and by means of factor-analytic studies. This provides the basis for a taxonomy of tests designed to provide separate measures of the two types of knowledge. Proposals for oral production tests, comprehension tests, judgements tests, tests of metalinguistic knowledge and tests derived from psycholinguistic research are examined and critiqued. The article concludes by suggesting there is a need for tests of L2 pragmatic knowledge to complement those available for grammar and offers a number of suggestions for the design of such tests.